SCHAUDER BASIS AND SEQUENCER SPACES IN GENERAL TOPOLOGICAL VECTOR SPACES - Moorthy, C. G.; Saminathan, I. R. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2025)
Minkowski functionals of balanced neighbourhoods of zero are used to define sequence spaces in which sequences are sequences in general non locally convex topological vector spaces. The classical result “Every basis in a complete metrizable \linebreak topological vector space is a Schauder basis” is generalized for such sequence spaces.